Beyond curated nature: the garden's potential in contemporary art (Itinera, 2025)
This essay explores the potential of the garden in contemporary art through a range of examples. Specifically, it examines three different ways in which the garden appears in contemporary art: as an exhibition space, an artistic product, and as a strategy. The discussion of these areas is framed by the context of the ecological crisis, which has fostered diverse engagements with issues such as biodiversity and sustainability. The selected artistic positions demonstrate various ways of addressing the ecological crisis and its associated questions, both on a conceptual level and through materiality.
Keywords: garden; biodiversity; plant-human relationship; artistic activism